2013
DOI: 10.21307/apex-2013-008
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Identification of Māori Gifted and Talented Students in Mainstream Schools

Abstract: This article describes a study into the identification of Māori students who are gifted and talented. The study used survey methodology and content analysis to establish the definitions and identification procedures used in mainstream schools in one region of Aotearoa New Zealand. The barriers and challenges these schools faced when identifying Māori students who are gifted and talented was also examined. The findings indicated that although some schools had definitions and identification practices which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…For STEM-related career aspirations in the United States, Saw, Chang and Chan (2018 [101]) found that socio-economic background, ethnicity and gender all had large effects on the aspirations to pursue a STEM-related career, as illustrated in Figure 3.3. Asian American boys from disadvantaged socio-economic backgrounds reported the highest aspirations to pursue a STEM-related career, even though this difference was not statistically significant from advantaged white boys' aspirations.…”
Section: Attitudes and Aspirationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For STEM-related career aspirations in the United States, Saw, Chang and Chan (2018 [101]) found that socio-economic background, ethnicity and gender all had large effects on the aspirations to pursue a STEM-related career, as illustrated in Figure 3.3. Asian American boys from disadvantaged socio-economic backgrounds reported the highest aspirations to pursue a STEM-related career, even though this difference was not statistically significant from advantaged white boys' aspirations.…”
Section: Attitudes and Aspirationsmentioning
confidence: 99%
“…Statistically significant differences compared to the reference group (white boys with higher SES) are shown in a darker tone. Source: Adapted from Saw, Chang and Chan (2018 [101]), Cross-Sectional and Longitudinal Disparities in STEM Career Aspirations at the Intersection of Gender, Race/Ethnicity, and Socioeconomic Status, https://doi.org/10.3102/0013189X18787818. 7 The prestige of occupations was measured using an index that considered the relative prestige level of the occupation, the minimum education required to enter the occupation, and the median income of those employed in the occupation.…”
Section: Figure 33 Aspirations To Pursue a Stem-related Careermentioning
confidence: 99%